2021
DOI: 10.29245/2578-3009/2021/s2.1103
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Polio Outbreak Response in Kenya, 2013 to 2015

Abstract: Background: Globally, tremendous improvement has been made in Polio eradication since its inception in 1988. For the third time in a decade, Kenya has experienced a Polio outbreak along the border with Somalia. The affected areas were in Garissa County, replete with previous occurrences in 2006 and 2012. This article, give an account of series of events and activities that were used to stop the transmission within 13 weeks, an interval between the first and the last case of the 2013 outbreak. Methods: In an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Haqqi et al [3] explored the impact of COVID-19 on the global polio eradication initiative in Pakistan. Nwogu et al [4] overviewed the outbreak of polio in Kenya from 2013 to 2015. Bandyopadhyaya et al [5] found the end game of polio eradication in final frontiers.…”
Section: Introductionmentioning
confidence: 99%
“…Haqqi et al [3] explored the impact of COVID-19 on the global polio eradication initiative in Pakistan. Nwogu et al [4] overviewed the outbreak of polio in Kenya from 2013 to 2015. Bandyopadhyaya et al [5] found the end game of polio eradication in final frontiers.…”
Section: Introductionmentioning
confidence: 99%